Predicting the mental health outcomes for Ebola first responders - Kirby, Adam; Hawkins, Merissa; David R., Black; J. Eric, Dietz (International Journal of Scientific World, 2017)
Purpose: The 2014 Ebola epidemic resulted in 26,683 cases and 11,022 deaths by May 6th, 2015. With first responders deploying from the United States to assist with the many challenges being faced in the field, they encountered a new set of traumatic events and situations that undoubtedly put them at risk for developing a mental disorder. Organizations must be prepared to provide mental health services for their employees and volunteers once they return.Approach: The authors questioned the potential prevalence of PTSD, ASD, and depression among returning first responders and which therapy method would be the most effective in terms of an individual’s recovered or improved condition. This was done through the use of AnyLogic® 7.0. An agent-based method to model the stress levels a first responder may experience while dealing with Ebola was used, where all responders begin in the healthy state and can develop mental health disorders. The therapy options tested were Cognitive Processing Therapy, Prolonged Exposure, and Group Based Exposure Therapy.Results: GBET for PTSD patients provided the most positive results in terms of condition recovery and improvement.Conclusion: The results showed evidence that the type of therapy used can drastically affect the individual’s mental health outcome.